Significance of Driver and Vehicle Key Performance Indicators on Organisational Performance and Customer Satisfaction: Case of Bulk Fuel Supply Chain in Zimbabwe - Munuhwa, Shakerod; Fuzane, Blessings Peace; Chikwere, David; Dzingai, Morris Emmanuel (The journal of contemporary issues in business and government, 2021)
Fuel supply is classified under critical and dangerous goods distribution. Truck Drivers (TD) and trucks are the two components involved in every stage of fuel road-distribution hence a focus on driver and vehicle key performance indicator measurements. The study examines the significance of driver key performance indicators and vehicle performance indicators on organisational performance and on customer satisfaction in the bulk fuel supply chain. A quantitative research methodology was conducted with 91 respondents drawn from the fuel sector. SMART PLS 3.3.3 was utilised for data analysis. The study found that there are positive and significant relationships between Vehicle KPIs and Driver KPIs; Driver KPIs and Organisational Performance (OP); Vehicle KPIs and OP; Driver KPIs and Customer service (CS), and OP and CS. The study also noted that Driver KPIs have significant mediating impact on OP. The mediating role of OP on CS was found to be insignificant.